(untitled) (Global Journal of Human-Social Science, 2025)
This paper evaluates the socialist character of contemporary China through the lens of Marxist theory and dialectical materialism Considering seminal works by Marx Engels and Lenin it is argued that the Chinese Communist Party s CCP project of a socialist market economy while demonstrably distinct from pure capitalism does not yet constitute socialism For instance the reintroduction of capitalist relations was deemed necessary by prominent CCP figures and Chinese intellectuals including Mao Zedong Deng Xiaoping Jin Huiming Chen Yun and Xue Muqiao as a means to enhance the productivity of the Chinese economy This enhanced productivity was considered imperative for achieving the future initial phase of socialist development China s present constitution is an evidence of this process showing internal contradictions between both modes of production This is due to the quantitative and qualitative changes that emerged on China s economic and political realms which can signalize a sublation